The Relationship Between Food Packaging Knowledge And Attitude Of Unp Culinary S1 Students To Using Plastic For Hot Food - Fauzi, Rifdahul; Faridah, Anni (Jurnal Pendidikan Tata Boga dan Teknologi, 2023)
This research is motivated by processed food products that are widely sold today packaged in various attractive forms. various types of materials, one of which is plastic. However, problems arise because there are people who use plastic packaging that is not in accordance with the standards for hot food which can endanger health. The purpose of this study was to describe: 1) the level of knowledge of food packaging, 2) the attitudes of students in using plastic for hot food, 3) to analyze the relationship between knowledge of food packaging and attitudes of S1 culinary students towards the act of using plastic for hot food. This type of research uses quantitative methods, correlational approaches. The population in this study were Catering students of 2019 and 2020. The research sample was 65 people who were selected by Proportional Random Sampling. Data is collected by distributing questionnaires via the Google form. The results showed: 1) the level of students' knowledge about food packaging was in the medium category with a percentage of 34%, 2) the attitude level of students towards the act of using plastic for hot food was in the medium category with a percentage of 43%, 3) there was a positive and significant relationship between knowledge of food packaging and students' attitudes towards the act of using plastic for hot food with a correlation value of rxy 0.621 and Tcount (6.283) > Ttable (1.999). meaning that the higher the knowledge, the higher the attitude of students in using plastic for hot food and vice versa.